Radar for Fully Autonomous Driving. - Markel, Matt (Artech House, 2022)
This is the first book to bring together the increasingly complex radar automotive technologies and tools being explored and utilized in the development of fully autonomous vehicles- technologies and tools now understood to be essential for the field to fully mature. You'll get a big-picture tour of the key radar needs for fully autonomous vehicles, and how achieving these needs is complicated by the automotive environment's dense scenes, number of possible targets of interest, and mix of very large and very small returns. You'll then be shown the challenges from and mitigations to radio frequency interference, an ever-increasing challenge as the number of vehicles with radars-and radars per vehicle-grow.
Keywords: Automated vehicles.; Radar.; elektronické knihy; electronic books